The changing paradigm of dyslipidaemia management - Ekanayaka, Ruvan (Universa Medicina, 2017)
The 2013 American College of Cardiology (ACC)/American Heart Association (AHA) guideline on the treatment of blood cholesterol to reduce atherosclerotic cardiovascular risk in adults,(1) effected a change in the paradigm of dyslipidaemia management, in that it no longer advocated a target based therapy but instead posited a primary clinical basis for initiation of statin therapy. The intensity of statin therapy too was guided by clinical risk criteria rather than by absolute values of the lipid profile.